Multiplex detection of foodborne pathogens by real-time loop-mediated isothermal amplification on a digital microfluidic chip. (June 2022) - Xie, Mei; Chen, Tianlan; Xin, Xiong; Cai, Zongwei; Dong, Cheng; Lei, Bo
Abstract: Rapid detection of foodborne pathogens is critical to assure food quality. In this study, a digital microfluidic (DMF) chip in combination with loop-mediated isothermal amplification (LAMP) was developed for multiplex detection of four common foodborne pathogens. The DMF chip contains ten reaction chambers with dehydrated primers targeting different genes for simultaneous amplification by LAMP in the volume of 2 μl/reaction with a detection limit of 10 2  CFU/ml for all target bacteria according to the 3σ criteria. Using spiked milk for validation, as low as 10 3  CFU/ml of all four pathogenic bacteria were detected simultaneously in a single test within 50 min. The proposed method exhibited higher sensitivity to the commercial benchtop LAMP method with the advantages of simpler operation, high efficiency, and miniaturization, showing great potential for point-of-care (POC) testing of various foodborne pathogens. Highlights: The DMF-LAMP assay was developed for multiplex detection of foodborne pathogens. The digital microfluidic platform is of high automation and flexibility. It is cost-effective and more sensitive than the benchtop LAMP method.